DESARROLLO DE LA EDUCACIÓN PARVULARIA EN CHILE - Jaime Caiceo (Associação Sul-Rio-Grandense de Pesquisadores em História da Educação (ASPHE), 2011)
Preschool education in Chile has its beginnings in the second half of the nineteenth century due to the German influence brought to Chile by José Abelardo Núñez. The first kindergarten was formed in a particular way. After that, the first public kindergarten, attached to the Normal School No. 1, was founded in 1906. At the same time, the austrian educator Maluschka Leopoldina was hired and the Froebelian method was used. At the University of Chile, in the 30s of the twentieth century, an improved movement was carried out by Irma Salas who studied for her doctorate in The United States with Dewey and brought the thought of the New School to the country. This event led to the establishment of the Kindergarten Teachers College in 1944 and its first principal was the prominent educator Amanda Labarca. This movement facilitated the establishment of nursery and childcare facilities throughout the country. This work has a historical character based on primary and secondary sources to show the development that the Chilean State has shown in relation to preschool education and the Children´s rights in Chile.